2019
DOI: 10.1097/cm9.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound features of basal cell carcinoma and its association with histological recurrence risk

Abstract: Background:Due to advances in high-frequency ultrasound technology, it is easier to detect fine structures of skin lesions. The aim of this study was to examine the ultrasonographic features and use recurrence risk stratification to assess the diagnostic performance of pre-operative ultrasound examination of basal cell carcinoma (BCC).Methods:This was a retrospective study. Forty-six BCC lesions underwent pre-operative ultrasound examination using 50- and 20-MHz probes. Ultrasonographic shape, margin, internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 17 publications
4
49
0
1
Order By: Relevance
“…Previous research found that HF‐US can show the depth of invasion of basal cell carcinoma, melanoma, and other cancers and the size of the lesion, providing important information for surgical resection. In addition, it can also stratify the basal cell carcinoma risk, which is helpful to guide clinical treatment, reduce recurrence, and improve the prognosis . In our study, HF‐US could show the infiltration depth and morphologic features of MF lesions, which provide important information for accurate staging of the lesions and is helpful for the choice of treatment.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous research found that HF‐US can show the depth of invasion of basal cell carcinoma, melanoma, and other cancers and the size of the lesion, providing important information for surgical resection. In addition, it can also stratify the basal cell carcinoma risk, which is helpful to guide clinical treatment, reduce recurrence, and improve the prognosis . In our study, HF‐US could show the infiltration depth and morphologic features of MF lesions, which provide important information for accurate staging of the lesions and is helpful for the choice of treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Based on previous reports, the following US features were adopted to evaluate MF: epidermal morphologic features (even or uneven), the infiltration depth (the deepest layer of the skin that the lesion infiltrated), the clarity of deep‐border boundaries (clearly or unclearly identified from the underlying skin structures), the homogeneity of internal echoes (homogeneous or inhomogeneous), posterior echoes (presence or absence of hypoechoic regions linearly distributed and perpendicular to the skin surface) and echogenic foci (presence or absence of pointlike hyperechoic structures <5 mm in diameter). To ensure that the lesion image was clear and completely displayed, we used 50‐MHz images whenever possible, especially when the lesions were in the early‐stage group, whereas 20‐MHz images were accepted when the lesions infiltrated into the deep dermis or subcutaneous tissue.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to sharing similar ultrasound characteristics with the rest of the included cases at 18 MHz, the BCC associated with this NSJ was eccentrically located and presented mixed anechoic‐hypoechoic echogenicity with some anechoic oval cystic areas and multiple hyperechoic spots. The histologic result was compatible with an adenoid‐cystic subtype of BCC 14–16 …”
Section: Resultsmentioning
confidence: 90%
“…Due to the wide variation in its clinical features, however, and particularly when both its manifestations and dermoscopic findings of its lesion are atypical, it may be challenging to differentiate SK lesions from other benign or malignant skin tumors. [ 1 , 2 ] We here report a case of SK of an adenoid type that initially imitated pigmented basal cell carcinoma (BCC) upon dermoscopy.…”
mentioning
confidence: 99%